Parkzeit - Kunstzeit. (Berlin : KaDeWe-Parkhaus Berlin, 1988)
Andresen, Sven ; Arlt-Aeras, Dietrich ; Bach, K. ; Breitwieser, Silvia ; Bucheler, Josef ; Büsch, Thomas ; Cane, Harry ; Fux, Mona ; Gilow, Fritz ; Hart, Chris ; Hector, Michael ; Hillig, Thomas ; Hoenerloh, Stefan ; Isleib, Günter ; Jost, Michael ; Jung, Joachim ; Kozlowski, Ryszard ; Krüger, Heike ; Kunzmann, Christoph ; Küster, Gerhard ; Linhardt, India ; Manthey, Elzbieta ; Miersch, Manfred ; Müller, Klaus-Peter ; Nehter, Brigitte ; Noll, Sabine ; Odin, Wolfram ; Pelzer, Matthias ; Projanowski, John ; Ramsa, Karten ; Sackenreuter, Ulrich ; Schmidt, Rainer ; Schmitter, Nora ; Schmorl, Petra-Lydia ; Schöning, Ziggy ; Schwedler, Thomas ; Skutnik, Roman ; Spiller, Dietmar ; Tiedje, Stefan ; Tümbach, Florian ; Ulbrich, Elke ; Völkers, Armin ; Wächter, Matthias ; Wassermann, Gudrun ; Weber, Claudius ; Werner, André ; Wetzlaugk, Michael ; Wieland, Jörg ; Yüko
Duits
Parkzeit - Kunstzeit, KaDeWe-Parkhaus Berlin, 23. Oktober 1988
boek